Dietary inflammatory index and all-cause mortality in adults with COPD: a prospective cohort study from the NHANES 1999–2018 - Tian, Tu-Lei; Zhi, Tian-Yu; Xie, Mei-Ling; Jiang, Ya-Lin; Qu, Xiang-Kun (Frontiers in Nutrition, 2024)
Background: Chronic inflammation is closely linked to Chronic Obstructive Pulmonary Disease (COPD); however, the impact of the Dietary Inflammatory Index (DII) on mortality among COPD patients remains uncertain.Objective: To assess the correlation between the DII and all-cause mortality in COPD patients using data from the National Health and Nutrition Examination Survey (NHANES).We conducted a retrospective cohort study on 1,820 COPD patients from the NHANES dataset (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). The influence of DII on mortality was evaluated using multivariate Cox regression, smoothing spline fitting, and threshold effect analysis. Subgroup analyses and E-values identified sensitive cohorts and assessed unmeasured confounding.Results: Over an average follow-up of 91 months, multivariate Cox regression models revealed a significant positive correlation between DII scores and mortality risk, with each unit increase in DII associated with a 5% higher risk of death (HR: 1.05, 95% CI: 1.00-1.09). Within the DII tertiles, individuals in the second tertile (T2: 1.23-2.94) experienced a 31% increase in mortality risk compared to those in the lowest tertile (T1: -5.28-1.23) (HR: 1.31, 95% CI: 1.09-1.58; P=0.005). A nonlinear relationship was identified, with significant risk increases below a DII of -0.884 (HR=1.649, 95% CI: 1.007-2.700; P=0.047). Both subgroup and sensitivity analyses corroborated the stability of these findings.Conclusions: DII is positively correlated with mortality risk in COPD patients, showing nonlinear characteristics and threshold effects, underscoring its prognostic value.